Usnic acid brief exposure suppresses cariogenic properties and complexity of Streptococcus mutans biofilms - Santosh Pandit; Mi-A Kim; Ji-Eun Jung; Hyeon-Mi Choi; Jae-Gyu Jeon (Biofilm)
Bacterial biofilms are highly structured surface associated architecture of micro-colonies, which are strongly bonded with the exopolymeric matrix of their own synthesis. These exopolymeric substances, mainly exopolysaccharides (EPS) initially assist the bacterial adhesion and finally form a bridge over the microcolonies to protect them from environmental assaults and antimicrobial exposure. Bacterial cells in dental biofilm metabolize dietary carbohydrates and produce organic acids. The blanket of exopolysaccharides over the bacterial communities hinders the buffering by saliva, contributing to the initiation of tooth decay followed by the progression of dental caries. Considering the current interest towards the use of natural antimicrobial agents to disarm the cariogenic properties of dental biofilm, this study evaluated the antimicrobial activity and the effect of twice daily brief exposure (1 min) of usnic acid on acid production, acid tolerance and development of 3-dimensional architecture of Streptococcus mutans biofilm. Herein, biofilms were briefly treated twice daily during biofilm development and biofilms were analyzed by using biochemical, microbiological and microscopic examination. Results obtained in this study showed a significant reduction in virulence properties of biofilm cells treated with usnic acid in compared to non-treated biofilms. Furthermore, twice daily brief exposure of usnic acid significantly disrupted the acid production and reduced the complexity of Streptococcus mutans biofilm by disrupting the EPS production. Brief exposure of usnic acid inhibited the production of glucosyltransferase (GTF) enzymes and their enzymatic activity leading to inhibition in production of EPS on the biofilm matrix. In conclusion, usnic acid treatment reduced the cariogenic properties and complexity of S. mutans biofilm by inhibiting acid production, acid tolerance and disrupting extracellular polysaccharide (EPS) formation, indicating its potential for preventing dental caries.